Systematic Review of Self-Regulated Learning in Physical Education on Mental Well-Being and Motivation - Fikri Firdiansyah; Tite Juliantine (Universitas Negeri Semarang, 2026)
This research is motivated by increasing academic pressure, which has resulted in a decline in students' mental well-being and learning motivation. Therefore, this study aims to examine the application of Self-Regulated Learning (SRL) in Physical Education learning and its impact on students' mental well-being and learning motivation. The methods used is Systematic Literature Review (SLR) with PRISMA approach through Google Scholar, Science Direct, and Scopus database searches . Subject in study This is 18 articles selected scientific based on criteria Inclusion and exclusion . Data analysis techniques were carried out through qualitative synthesis by identifying patterns, themes, and relationships between research findings.The results of the study indicate that the implementation of SRL in Physical Education is carried out through goal-setting, self-monitoring, and self-evaluation strategies, as well as through the learning stages of observation, emulation, self-control, and self-regulation. The implementation of SRL has been proven to have a positive impact on students' mental well-being, such as improving self-regulation, emotional stability, self-confidence, and the ability to cope with stress. In addition, SRL also has a significant effect on students' learning motivation, especially intrinsic motivation, by increasing autonomy and active involvement in learning.Thus, the integration of SRL in Physical Education learning is an effective and holistic approach in supporting students' physical, mental, and learning motivation development.